Perancangan Iklan Gim Mobile Activia Sebagai Media Periklanan Android - Mochammad Amirul Hakim (DeKaVe, 2014)
Age of information require people to think fast. Slowly, both electronic ads and print ads are losttheir attraction. So that new media for advertise need to renew somehow.Game isn’t kind of luxurious toys these days. Most people can play it freely or buy with their smartphones,everywhere at anytime. They can play, share, update, even play in a group on different state with internettechnology features on mobile phone.This design is try to combine advertise with mobile game as media. Using the addictive of the game, peoplecan get more features to win the game with buy then scanning QR code within product package. The objectof this design is Activia. Activia is healthy yogurt product. The goal is this design is using mobile game foradvertising to sell product more effective and efficiently.Keywords: Activia, Gim, Food, Mobile, Yogurt.